International study to develop the WOUND‐Q patient‐reported outcome measure for all types of chronic wounds. Issue 4 (10th March 2021) - Klassen, Anne F.; van Haren, Emiel L. W. G.; van Alphen, Tert C.; Cano, Stefan; Cross, Karen M.; van Dishoeck, Anne‐Margreet; Fan, Kenneth L.; Michael Hoogbergen, Maarten; Orgill, Dennis; Poulsen, Lotte; Ahm Sørensen, Jens; Squitieri, Lee; et al.
Abstract: Patient‐reported outcome measures (PROMs) for chronic wounds mainly focus on specific types of wounds. Our team developed the WOUND‐Q for use with all types of wounds in any anatomic location. We conducted 60 concept elicitation interviews with patients in Canada, Denmark, the Netherlands, and the United States. Analysis identified concepts of interest to patients and scales were formed and refined through cognitive interviews with 20 patients and input from 26 wound care experts. Scales were translated into Danish and Dutch. An international field‐test study collected data from 881 patients (1020 assessments) with chronic wounds. Rasch measurement theory (RMT) analysis was used to refine the scales and examine psychometric properties. RMT analysis supported the reliability and validity of 13 WOUND‐Q scales that measure wound characteristics (assessment, discharge, and smell), health‐related quality of life (life impact, psychological, sleep impact, and social), experience of care (information, home care nurses, medical team, and office staff), and wound treatment (dressing and suction device). The WOUND‐Q can be used to measure outcomes in research and clinical practice from the perspective of patients with any type of wound.